INTEGRATING ASSESSMENT AND INSTRUCTION: DYNAMIC ASSESSMENT AND ITS CRITICISMS EXAMINED - Hosna Hosseini; Behzad Ghonsooly (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
Dynamic Assessment has recently been voiced of constructivism, the socio-cultural theory of learning. This article, challenging the psychometric and product-based test, makes an attempt to delve into the epistemological and ontological theories of Dynamic Assessment (DA) and their criticisms. DA is the offspring of Vygotsky's theory of the Zone of Proximal Development (ZPD) and Feuerstein's mediated learning experience (MLE). It emphasises constructing a future through mediations. Interestingly, this development-oriented process of collaboration relies on the unification of instruction and assessment which is a strong threat to the reliability of the psychometric tests. This study also deals with the battle of views on DA. It discusses the appealing face of DA embracing ethical values, fairness and social equity, and the process based assessment. It also argues the negative face of DA comprising modifiability, interventionism, and stability. It finally concludes that each system should be criticised by certain criteria. Faced with the scarcity of research both theoretically and empirically, the critical analysis of this new generation of test in an L2 setting might be helpful for further discussions, suggestions and implications in the second language learning arena.